Lanthanide-Doped Upconversion Nanoparticles for Super-Resolution Microscopy - Dong, Hao; Sun, Ling-Dong; Yan, Chun-Hua (Frontiers in Chemistry, 2021)
Super-resolution microscopy offers a non-invasive and real-time tool for probing the subcellular structures and activities on nanometer precision. Exploring adequate luminescent probes is a great concern for acquiring higher resolution image. Benefiting from the atomic-like transitions among real energy levels, lanthanide-doped upconversion nanoparticles are featured by unique optical properties including excellent photostability, large anti-Stokes shifts, multicolor narrowband emissions, tunable emission lifetimes, etc. The past few years have witnessed the development of upconversion nanoparticles as probes for super-resolution imaging studies. To date, the optimal resolution reached 28 nm (/36) for single nanoparticles and 82 nm (/12) for cytoskeleton structures with upconversion nanoparticles. Compared with conventional probes such as organic dyes and quantum dots, upconversion nanoparticles-related super-resolution microscopy is still in the preliminary stage, and both opportunities and challenges exist. In this perspective article, we summarized the recent advances of upconversion nanoparticles for super-resolution microscopy, and projected the future directions of this emerging field. This perspective article should be enlightening for designing efficient upconversion nanoprobes for super-resolution imaging and promote the development of upconversion nanoprobes for cell biology applications.